1982
DOI: 10.1073/pnas.79.10.3260
|View full text |Cite
|
Sign up to set email alerts
|

gamma Heavy chain disease in man: cDNA sequence supports partial gene deletion model.

Abstract: Human y heavy chain disease (HCD) is characterized by the presence in serum of a short monoclonal Ig y chain unattached to light chains. Although most HCD proteins have internal deletions, in some the defect is NH2-terminal. The OMM v3 HCD serum protein is of the latter type, having undergone an extensive NH2-terminal deletion with a sequence starting within the hinge. A cell line synthesizing the OMM protein has enabled us to study the biogenesis ofthe abnormal molecule. In vitro translation ofisolated mRNA y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 43 publications
(26 reference statements)
3
31
0
Order By: Relevance
“…G3m (21) is likely to be determined by a Pro?Leu mutation at position 291 (CH2 domain). The same conclusion was drawn from the analysis of the OMM protein 42,43 and a previous sequencing of CH2-CH3 domains. 13 We exclude the involvement of amino acid Asn384, because it is coded by one G3m 5,10,11,13,14 Mandenka sequence (M6), and of Arg435-Tyr436, because they are located on CH3: enzymatic digestions indicate that G3m (21) is detected on the Fc (CH2-CH3), but not on the Fc' (CH3) fragments.…”
Section: Amino Acids Involved In G3m Allotypysupporting
confidence: 52%
“…G3m (21) is likely to be determined by a Pro?Leu mutation at position 291 (CH2 domain). The same conclusion was drawn from the analysis of the OMM protein 42,43 and a previous sequencing of CH2-CH3 domains. 13 We exclude the involvement of amino acid Asn384, because it is coded by one G3m 5,10,11,13,14 Mandenka sequence (M6), and of Arg435-Tyr436, because they are located on CH3: enzymatic digestions indicate that G3m (21) is detected on the Fc (CH2-CH3), but not on the Fc' (CH3) fragments.…”
Section: Amino Acids Involved In G3m Allotypysupporting
confidence: 52%
“…In the case of BiP-H-chain association, BiP seems to require a site within the CH1 domain of H chains and is no longer associated with H chain after the L-chain-Hchain pairing process (6,8). Consistent with this scheme is the uniform deletion of all or part of the CH1 domain among the secreted human H* chains (4,(9)(10)(11)(12). As all transported H* chains thus far tested fail to interact with BiP with normal affinity (8), it has been suggested that such truncated H* chains can be secreted by virtue of the inability of BiP to recognize them and prevent their movement out of the ER.…”
mentioning
confidence: 54%
“…Intracellular transport of the A* chains is thus unencumbered from the normal mechanism governing transport of native H chains, leading to the expression of the unusual pz-chain-only phenotype for cellsurface immunoglobulin. While it is known that both mouse and human CA1 domain-deleted A chains can be secreted without being paired with L chain (8)(9)(10)(11), the ability of these truncated ,u chains to be expressed at the cell surface is currently unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previously reported case of patient OMM with ␥3 heavy-chain disease (2,(7)(8)(9), the deleted ␥3 protein present in serum started at the N-terminus of the hinge region (residue 226 in normal ␥3), whereas the complementary DNA (cDNA) and protein product of cloned cells, as well as that translated from the respective messenger RNA, showed that an additional segment consisting of the 14 N-terminal amino acid residues of V H plus a proline at position 15 was directly attached to the hinge. This apparent discrepancy was apparently caused by posttranslational proteolysis.…”
mentioning
confidence: 98%